2021
DOI: 10.3946/kjme.2021.200
|View full text |Cite
|
Sign up to set email alerts
|

Stress and associated factors with received and needed support in medical students during COVID-19 pandemic: a multicenter study

Abstract: Purpose: The coronavirus disease 2019 (COVID-19) pandemic is a global health crisis that has impacted daily life due to the policies created to contain the outbreak. Recent studies showed that medical students, a high-stress population, experienced deteriorated mental well-being during the pandemic. The aim of the present study was to assess stress and the need for support among Thai medical students during the COVID-19 pandemic, as a multicenter study.Methods: The present study was a cross-sectional questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
2
10
0
1
Order By: Relevance
“…Several other studies have pointed to a significant difference between genders in terms of anxiety, pointing to higher levels of anxiety and stress in females just like in our sample [12,15,[17][18][19][20]23,24,[27][28][29]37]. However, we also found some studies that did not observe statistically significant differences between genders in terms of anxiety and stress in their samples [13,14,16].…”
Section: Comparison Of Results By Genderssupporting
confidence: 51%
See 1 more Smart Citation
“…Several other studies have pointed to a significant difference between genders in terms of anxiety, pointing to higher levels of anxiety and stress in females just like in our sample [12,15,[17][18][19][20]23,24,[27][28][29]37]. However, we also found some studies that did not observe statistically significant differences between genders in terms of anxiety and stress in their samples [13,14,16].…”
Section: Comparison Of Results By Genderssupporting
confidence: 51%
“…Gender, especially being female, was shown in several studies to be a risk factor for anxiety and stress [12,15,[17][18][19][20]23,24,[27][28][29] as well as depressive symptoms [17] during the COVID-19 pandemic. Females tend to be more predisposed to express their feelings and are more likely to experience different social expectations, pressures, and gender equalityrelated positions [23].…”
Section: Introductionmentioning
confidence: 99%
“…Students who lived with their family were two and a half times (OR = 2.57) more likely to self-report severe stress in relation to their colleagues who lived alone and perceived their stress as moderate or mild. On the contrary, research conducted in Thailand [ 30 ] showed that stress reduction is more successful if students are provided with some form of social support and assistance. The transition of society, the lack of social support within some families, and the value system that has reigned in Serbia recently might be partly responsible for the ongoing situation, while in countries with a very expressed collectivist culture, such as Indochina, the value of social support has not declined.…”
Section: Discussionmentioning
confidence: 99%
“…In March 2020, the World Health Organization (WHO) declared the outbreak of COVID-19 as a pandemic [ 2 ]. It is a global health crisis that has impacted on daily life, due to the policies created to contain the outbreak [ 3 ]. Strict rules to protect the population from the virus, including social and physical distancing, were introduced as the countermeasures.…”
Section: Introductionmentioning
confidence: 99%